2020
DOI: 10.1177/2058739220935280
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anti-inflammatory properties of Mayan propolis

Abstract: Introduction Propolis has been used traditionally for different human diseases and even recently as dental biomaterials because of its antibacterial, antimycotic, and anti-inflammatory properties. However, a proper correlation between in vitro and in vivo anti-inflammatory properties has not been clearly established. Methods The composition of propolis was determined by high-performance liquid chromatography–ultraviolet mass spectrometry (HPLC-UV-MS). Viability of ethanolic propolis solution was evaluated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In this regard, the bactericidal effect of propolis has been attributed to the presence of flavonoids being more effective against Streptococcus salivarius rather than Streptococcus mutans [ 35 ]. In this line of thought, we have reported that the major components of propolis were pinocembrin, pinobanksin-3-O-acetate, and pinobanksin-3-O-propionate, which can be partly responsible for its mild antibacterial behavior [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, the bactericidal effect of propolis has been attributed to the presence of flavonoids being more effective against Streptococcus salivarius rather than Streptococcus mutans [ 35 ]. In this line of thought, we have reported that the major components of propolis were pinocembrin, pinobanksin-3-O-acetate, and pinobanksin-3-O-propionate, which can be partly responsible for its mild antibacterial behavior [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous results from our group demonstrated the in vitro anti-inflammatory activity of propolis, as the levels of pro-inflammatory IL-1β, IL-6, and TNF-α were low, while the levels of IL-10 and IL-4 were high. Overall, the clinical performance of the propolis MPAC will depend not only on its antibacterial properties, but also on its antioxidant activity and anti-inflammatory properties [ 32 ]. In addition, it has been reported that propolis is used for the treatment of candidiasis, acute necrotizing ulcerative gingivitis, gingivitis, periodontitis, and pulpitis in dentistry, and there are reports regarding the antibacterial effects of propolis on methicillin-resistant Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This restraining effect appears to be mediated through the modulatory influence exerted by propolis upon mononuclear macrophages most likely via the engagement of TNF-R1 receptor [66,68]. Congruent with this proposition, propolis treatment has been noted by few independent investigations to considerably obviate the profound upregulation of TNF-α levels in several human and murine monocyte/macrophage cells such as THP-1 [69], J774A.1 [70], and peritoneal macrophages [71]. However, the detailed molecular underpinnings by which propolis regulate the TNF-α signaling pathway remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%